Intel Economics - Paul S. Segerstrom (The Research Institute of Industrial Economics (IUI), 1999)
This paper presents a model to explain why both industry leaders and follower firms often invest in R&D and explores the welfare implications of these R&D investment choices. Regardless of initial conditions, the equilibrium path in this model involves gradually convergence to a balanced growth path and R&D subsidies have no effect on the balanced growth rate. Nevertheless, it is always optimal for the government to intervene by subsidizing the R&D expenditures of industry leaders and taxing the R&D expenditures of follower firms. Without government intervention, market forces generate too much creative destruction.
Keywords: O32; O41; 330; Economic growth; R&D; Forschung; Investition; Wohlfahrtsanalyse; Theorie